Disaggregation kinetics of a peat humic acid: mechanism and pH effects - Avena, Marcelo Javier (2002)
Fluorescence correlation spectroscopy was used to study the disaggregation kinetics of a peat humic acid (PPHA) at several pH. FCS measures diffusion coefficients of fluorescent molecules and aggregates, thus allowing for the determination of disaggregation rates with a temporal resolution of seconds to minutes. Disaggregation was initiated by dilution of a peat concentrate consisting of a mixture containing 80% large aggregates (average hydrodynamic radius, rH, of about 300 nm) and free monomers (average rH of about 1 nm). Upon dilution at different pH values, aggregate size decreased, and the proportion of free monomers in solution increased until complete disaggregation occurred. The mechanism appeared to involve the release of monomers from the surface of the aggregates. The pH markedly affected the disaggregation rate. Complete disaggregation took 1 month at pH 3.6, took less than 1 h at pH 5.6, and was extremely rapid in alkaline solutions. The results suggested that at least two processes were operating in parallel with the overall rate being the sum of both processes. At pH higher than 4.5, the disaggregation rate increased more than 3 orders of magnitude per pH unit increase. For concentrations lower than 30 mg L-1, the equilibrium condition for the PPHA was complete disaggregation even for a pH as low as 3.6.